Study of the yeast cytosolic Hsp70-system in protein homeostasis and life span regulation - The misfolding protein marker gus1-3-GFP and the metacaspase Mca1-GFP during mid-exponential growth in yeast Hsp70-mutant yeast strains - Hanzén, Sarah; Vielfort, Katarina; Andersson, Rebecca; Nyström, Thomas (University of Gothenburg, 2020)
Our study aims to answer the question "Which functions of the Hsp70 class of molecular chaperones are essential for yeast to maintain a standard replicative life span?". To answer this question, we utilised the disparate functions of the Hsp70's Ssa1 and 2 and their paralog Ssa4 in a yeast strain that lacks Ssa1/2 but has an ectopically increased production of Ssa4. We have gathered data on the behaviour of several different markers for protein aggregation under different circumstances, as well as data on proteins from other classes of molecular chaperones. The bulk of the data is in the form of multichannel microscopy images from widefield microscopy, with a few sets of western blots of protein extracts.

Fluorescence microscopy of live yeast cells at mid-exponential growth. All strains produce the aggregate marker protein gus1-3-GFP or the metacaspase Mca1 tagged with GFP (Mca1-GFP)

The dataset was collected through fluorescence microscopy.
The image files are provided in Carl Zeiss Image format (.czi).

Vi har systematiskt studerat vilka funktioner hos de cytosoliska molekylära chaperonerna av klassen Hsp70 hos jäst som krävs för att upprätthålla en normal livslängd.

Fluorescensmikroskopi av levande jäst i mitten av den exponentiella tillväxtfasen. Jästen är odlad i rikt medium (YP) med 2 % glukos som kolkälla. Alla avbildade stammar producerar det felveckade markörproteinet gus1-3-GFP eller metacaspaset Mca1 taggat med GFP (Mca1-GFP).
Datasetet har samlats in genom fluorescensmikroskopi.
Bildfilerna är i Carl Zeiss Image-format (.czi).
Studier av det cytosoliska Hsp70-systemet från jäst och dess roll i proteinhomeostas och reglering av livslängd - Det felveckande markörproteinet gus1-3-GFP och metacaspaset Mca1-GFP avbildat under mitten av den exponentiella tillväxtfasen i Hsp70-mutanta jäststammar
Keywords: Molecular Chaperones; Molekylära chaperoner; HSP70 Heat-Shock Proteins; HSP70-värmechockproteiner; Proteostasis Deficiencies; Proteostasbrist; Cell Biology; Cellbiologi; Microbiology; Mikrobiologi; Cell and Molecular Biology; Cell- och molekylärbiologi; Molecular Biology; Molekylärbiologi